A 2.4/5.2-GHz Concurrent Dual-Band CMOS Low Noise Amplifier - Sattar, S. (Institute of Electrical and Electronics Engineers Inc., 2017)
A concurrent dual-band low-noise amplifier (LNA) targeted for W-LAN IEEE 802.11 a/b/g standards is designed using 0.13- μm CMOS process. To attain the power-constrained simultaneous noise and input matching at 2.4 and 5.2 GHz, cascode common source inductive degeneration topology is adopted. The LNA achieves input reflection coefficients of -16.8 and -19.4 dB, forward gains of 19.3 and 17.5 dB at 2.4 and 5.2 GHz, respectively. Furthermore, the LNA exhibits noise figures of 3.2 and 3.3 dB with input 1-dB compression points of -29.6 and -28.2 dBm, while third-order input intercept points of -20.1 and -18.1 dBm at 2.4 and 5.2 GHz, respectively. The LNA dissipates 2.4 mW of power from a 1.2-V supply. © 2013 IEEE.